Developing a multi·strand framework and test for assessing year 4 pupils' proficiency in measurement formulae. - Chew , Cheng Meng (Universiti Sains Malaysia, 2016)

(untitled)
The study focused on profiling and determining if there were any significant differences in Year 4 pupils' levels of proficiency perimeter, area and volume formulae based on the four demographic variables, which are type of school, location of school mathematics achievement level and gender. The results of this study provide a complex pattern in the levels of proficiency measurement formulae based on the four demographic variables. Thus, it is recommended that the levels of proficiency measurement formulae in association with other factors, such as supplementary tuition, parental guidance, socio-economic status and parents' educational level can be investigated in future studies.